Understanding the elusive protein corona of thermoresponsive nanogels. (9th October 2018) - Miceli, Enrico; Kuropka, Benno; Rosenauer, Christine; Osorio Blanco, Ernesto R; Theune, Loryn E; Kar, Mrityunjoy; Weise, Christoph; Morsbach, Svenja; Freund, Christian; Calderón, Marcelo
Aim: We analyzed the protein corona of thermoresponsive, poly( N -isopropylacrylamide)- or poly( N -isopropylmethacrylamide)-based nanogels.Materials & methods: Traces of protein corona detected after incubation in human serum were characterized by proteomics and dynamic light scattering in undiluted serum.Results: Apolipoprotein B-100 and albumin were the main components of the protein coronae. For dendritic polyglycerol-poly( N -isopropylacrylamide) nanogels at 37°C, an increase in adsorbed immunoglobulin light chains was detected, followed by partially reversible nanogel aggregation. All nanogels in their hydrophilic state are colloidally stable in serum and bear a dysopsonin-rich protein corona.Conclusion: We observed strong changes in NG stability upon slight alterations in the composition of the protein coronae according to nanogel solvation state. Nanogels in their hydrophilic state possess safe protein coronae.